2015
DOI: 10.1109/tmag.2014.2359248
|View full text |Cite
|
Sign up to set email alerts
|

Quantities Affecting the Behavior of Vibrational Magnetostrictive Transducers

Abstract: Through the conversion from mechanical to ele ctrical energy it is possible to monitor a vibrating machine of any kind, by exploiting the mechanical energy produced by the vibration. To this end, one can use direct force devices inserted in the supports or in the kinematic chain of the vibrating contrivance, or cantilever devices with seismic masses. Regarding the devices of the first t ype, the maximization of the electrical output depends on various parameters. This work, through a combined experimental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…This generated 2.17 V (peak value, using a coil of 267 turns) with a 10 MPa compressive load. The power Zucca et al [79] analyzed the factors that influence the performance of a Terfenol-D rod and showed that the induced electrical current and power have a complex dependence on several quantities, namely the coil characteristics, type of permanent magnets, and characteristics of the mechanical excitation. The power Zucca et al [79] analyzed the factors that influence the performance of a Terfenol-D rod and showed that the induced electrical current and power have a complex dependence on several quantities, namely the coil characteristics, type of permanent magnets, and characteristics of the mechanical excitation.…”
Section: Terfenol-dmentioning
confidence: 99%
See 1 more Smart Citation
“…This generated 2.17 V (peak value, using a coil of 267 turns) with a 10 MPa compressive load. The power Zucca et al [79] analyzed the factors that influence the performance of a Terfenol-D rod and showed that the induced electrical current and power have a complex dependence on several quantities, namely the coil characteristics, type of permanent magnets, and characteristics of the mechanical excitation. The power Zucca et al [79] analyzed the factors that influence the performance of a Terfenol-D rod and showed that the induced electrical current and power have a complex dependence on several quantities, namely the coil characteristics, type of permanent magnets, and characteristics of the mechanical excitation.…”
Section: Terfenol-dmentioning
confidence: 99%
“…Viola et al [78] proposed an approach to designing a Terfenol-D power generator for energy harvesting from traffic vibration and validated it experimentally. The power Zucca et al [79] analyzed the factors that influence the performance of a Terfenol-D rod and showed that the induced electrical current and power have a complex dependence on several quantities, namely the coil characteristics, type of permanent magnets, and characteristics of the mechanical excitation. In particular, the magnetic and mechanical bias were of great importance in terms of power (82.8 mW).…”
Section: Terfenol-dmentioning
confidence: 99%
“…The proposed equivalent strain/stress approach is tested with the three multiaxial stress configurations σequ, σsh1 and σsh2 shown in (3), when σ varies between -30 and +30 MPa. The idea is to obtain the relative permeability μr = B/(μ0Hx) under the three stress configurations simply by interpolating from the μr(σ) relationship measured under σuni (markers in the top-left part of Fig.…”
Section: Equivalent Strain/stressmentioning
confidence: 99%
“…AGNETO-MECHANICAL interaction causes additional losses and permeability degradation in electrical machine cores [1]. On the other hand, the same effects can be utilized for harvesting electrical energy from mechanical vibration [2], [3]. Complex multiaxial strains and stresses may occur in such applications, but identification measurements are most commonly available only under uniaxial stress parallel to the magnetic field [4]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…ECENTLY MANY energy harvesting systems based on magnetostrictive materials have been proposed [1][2][3][4][5][6][7] . In magnetostrictive materials, the application of an external mechanical force induces a change in the level of magnetization and consequently an electromotive force (emf) is generated.…”
Section: Introductionmentioning
confidence: 99%